Efeitos do treinamento aeróbico na máxima fase estável de lactato e no tempo de exercício até a fadiga - Thiago Teixeira Mendes (2009)
Maximal lactate steady state (MLSS) is considered as the gold standard to evaluate and predict aerobic performance. However, few studies have investigated the influence of aerobic training in variables associated to MLSS and time until fatigue. The aim of the present study was to verify the influence of six weeks of aerobic training in the variables associated to MLSS and in the time of exercise until fatigue. Twenty one men, non-participants of any aerobic training were divided into two groups: control group (GC; n=8) (25.1±0.9years; 70.1±3.5kg; 1.79±0.02m; 45.2±1.5mL.kg-1.min-1) and training group (GT; n=13) (22.5±0.7years; 72.9±1.9kg; 1.76±0.02m; 44.9±1.3mL.kg-1.min-1). All tests were performed on a cycle ergometer in a temperate environment (21-24ºC; 50-70% of relative humidity) with a 48-72h interval between tests. The volunteers performed an incremental test to evaluate the maximum oxygen uptake (VO2MAX), two to five constant tests to identify MLSS and a test until fatigue on the MLSS intensity. Afterwards they were submitted to six weeks of treatment (aerobic training or control). Then, they performed all the same tests executed initially. MLSS was considered the highest exercise intensity in which a maximal variation of 1mM of lactate between minutes 10 and 30 of exercise was observed. After determination of MLSS, all subjects performed an exercise until fatigue at this intensity. Training consisted of six weeks of aerobic training, three times a week at the MLSS intensity, with initial duration of 24min and increments of 3min per week. After aerobic training GT increased VO2MAX in 10.9% and MLSS intensity in 14.7%. No differences were observed after the treatment period in heart rate, rating of perception exertion (RPE), lactataemia and oxygen uptake at MLSS in both groups. There was no change in time until fatigue after the treatment in GC (63.1±8.5 and 56.8±4.6min; before and after, respectively) and GT (70.5±8.9 and 67.3±7.4min). At the time of fatigue, no variables reached their limiting values. Fatigue was associated to the integrated model, in which several factors can contribute to the interruption of exercise without failure in homeostasis. We conclude that six weeks of aerobic training at MLSS increased VO2MAX and MLSS intensity, but there was no difference in lactataemia and time to fatigue.